The use of Whatsapp group in class-related information sharing through academic discussion / Johan@Eddy Luaran, Jasmine Jain and Norilyani Abd Rahman - Luaran, Johan@Eddy; Jain, Jasmine; Abd Rahman, Norilyani (Penerbit UiTM (UiTM Press), 2016)
The world nowadays is acquainted with the term 'technology' as humans are surrounded with sophisticated gadgets which may help to ease communication amongst human beings. The purpose of this study was to investigate the students 'perceptions on the use of WhatsApp Group in class-related information sharing through academic discussions. Apart from that, this study also examined the impacts of using WhatsApp Group in discussion related to learning as well as to investigate whether or not WhatsApp Group may improve students' learning process. This study was a quantitative study conducted in a college in Perak. Questionnaires were distributed to 150 respondents by using random sampling. The data were analysed by using the SPSS Version 22.0. The results indicated that students have positive perceptions and it gives positive impacts to students 'learning by using WhatsApp Group in Class-related Information sharing through academic discussions. The result also shows that WhatsApp Group may lead to students' improvement in their learning process.